Non-base wage components as a source of wage adaptability to shocks : evidence from european firms, 2010-2013 - Babecky, Jan (2018)
This paper provides evidence on the role of non-base wage components as a channel for firms to adjust labour costs in the event of adverse shocks. It uses data from a firm-level survey for 25 European countries that covers the period 2010–2013. We find that firms subject to nominal wage rigidities, which prevent them from adjusting base wages, are more likely to cut non-base wage components in order to adjust labour costs when needed. Firms thus use non-base wage components as a buffer to overcome base wage rigidity.We further show that while non-base wage components exhibit some degree of downward rigidity, they do so to a lesser extent than base wages.